Development of Democracy & Phenomenon of Single Candidate in Regional Election (Pilkada) - Sarno Wuragil; Widayati Widayati (Law Development Journal, 2021)
This study aims to answer the problem. What are the factors that cause the emergence of a single candidate in the 2020 Regent and Deputy Regent Election in Wonosobo, what are the obstacles in the regeneration of political parties in Wonosobo Regency? And What is the relationship between a single candidate for regional head elections with the development of Indonesian democracy? This research method uses a juridical-empirical approach. Based on the research, it can be concluded that the Election of Regent and Deputy Regent in Wonosobo Regency is only able to carry one candidate pair. Juridical factors underlie the existence of a single candidate pair. This is due to the constraints on regeneration by political parties which are said to be sudden and the traditional system of selecting candidates. This effect has a significant impact on the quality of democracy in Wonosobo Regency.